SISTEM INFORMASI REGISTER PENDIRIAN BADAN HUKUM CV PADA PENGADILAN NEGERI KLAS 1A PADANG - Rifa Turaina; Isteti Murni; Ila Fur Rahmah (Universitas Negeri Padang, 2018)
Information technology continues to develop along with the ability of humans to design and make computers and are able to provide solutions to problems in various fields. Based on this research, the system of registering the establishment of a legal entity CV in Padang Class 1A District Court still has many problems, where each time there is a certificate of incorporation of the CV legal entity that is only recorded in the register book that has been provided. So during the recording process data errors often occur, because there is no database as a place to store data registering a good CV legal entity. The purpose of this study is to design a system using the Java programming language. Data collection methods used questionnaires and interviews conducted on Padang District Court 1A District Court legal staff. The results of this research are an application program which can later provide convenience in processing and restating the information needed and provide one solution to improve the performance of employees of the Padang 1A Class District Court